Evidence for a Magnetic Flux Rope in Observations of a Solar Prominence-Cavity System - Jibben, Patricia R.; Reeves, Katharine K.; Su, Yingna (Frontiers in Astronomy and Space Sciences, 2016)
Coronal cavities are regions of low coronal emission that usually sit above solar prominences. These systems can exist for days or months before erupting. The magnetic structure of the prominence-cavity system during the quiescent period is important to understanding the pre-eruption phase. We describe observations of a coronal cavity situated above a solar prominence observed on the western limb as part of an Interface Region Imaging Spectrograph (IRIS) and Hinode coordinated Observation Program (IHOP 264). During the observation run, an inflow of hot plasma observed by the Hinode X-Ray Telescope (XRT) envelopes the coronal cavity and triggers an eruption of chromospheric plasma near the base of the prominence. During and after the eruption, bright X-ray emission forms within the cavity and above the prominence. IRIS and the Hinode EUV Imaging Spectrometer (EIS) show strong blue shifts in both chromospheric and coronal lines during the eruption. The Hinode Solar Optical Telescope (SOT) Ca II H-line data show bright emission during the ejection with complex, turbulent, flows near the prominence and along the cavity wall. These observations suggest a cylindrical flux rope best represents the cavity structure with the ejected material flowing along magnetic field lines supporting the cavity. We also find evidence for heating of the plasma inside the cavity after the flows. A model of the magnetic structure of the cavity comprised of a weakly twisted flux rope can explain the observed loops in the X-ray and EUV data. Observations from the Coronal Multichannel Polarimeter (CoMP) are compared to predicted models and are inconclusive. We find that more sensitive measurements of the magnetic field strength along the line-of-sight are needed to verify this configuration.